Implementation of 5R, Reward And Working Safety On Productivity Construction Project - Dewi Tamara; Aditya Cahyo Nugroho; Denny I. Ardiansyah (Kusuma Negara Business School, 2021)
The development of construction businnes is highly increased. It is caused by the improvement of productivity on the project division of power plant and industrial plant. The achievement of productiovity effort is a performance measurement of a corporation. The study aims at investigating the impact or contribution of 5R implementation, Rewards, and Working Safety on productivity of commissioning working stage on construction project of PT Wijaya Karya (Persero) Tbk. The method of the study was quantitative using multiple regression statistic test to know the influence among variables. Sample of the study were workers of Operation Directorate II having duty on Engineering and Commissioning functions. The result of the study showed that the implementation of 5R, rewards and working safety either simulatenously or partially had positive and significant influence on the productivity of the commissioning working stage on the construction project of PT Wijaya Karya (Persero) Tbk.